AUTOMATION OF INDUSTRIAL (IOT) AND CYBER SECURITY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
our everyday lives, it could be easy to gain personal information or know the information of the individualbusiness network community in order to allow cyber security attacks in our country to collapse and lose control. Cyberattacks are limitless in the IT field or in companies of the network. As a matter of fact, many business industries use IoT thatis used to link and pass data from one computer to another that is called MACHINE TO MACHINE communication whilethe transfer of data cyber security threats are transferred so that the attacker can access and track the data. We have suggestedindustrial automation using IoT by including cyber security in this article. The key aim of this paper is to allow dataprotection through the use of IoT in industries and to share or transfer protected messages.